Fast Walk Exercise on Blood Pressure Changes in Women With Diabetes Mellitus - Sriwahyuni Sriwahyuni; Sri Darmawan; Indra Dewi; Ria Indriana Sukri (The International Science of Health Journal, 2023)
Diabetes Mellitus (DM) is a metabolic disorder of chronic hyperglycemia, often accompanied by the onset of metabolic syndrome, namely hypertension which can trigger and exacerbate cardiovascular complications so it is necessary to implement 4 pillars of management namely education, medical nutrition therapy, physical exercise and medical therapy Nonpharmacological interventions are proven to be the best for prevention and hypertension treatment such as Aerobics (Fast Walking) which can be done for 90–150 minutes/week. The type of research used is quantitative research using the Quasi Experimental Pretest-Posttest Control Group Design. The sample size is 40 people.Brisk walking has an influence on changes in blood pressure in diabetic women so it is hoped that light sports activities will be increased as one of the therapies in non-pharmacological treatment of diabetes mellitus patients.